Study of 3C-SiC Lateral Double Diffusion MOSFET For Current Enhancement Based On Fixed Oxide Charge Inside SiO2 Layer. - Bansal, Meenal (My University, 2010)
The fast growing market for semiconductor devices and the high costs for fabricating the devices give rise to ongoing miniaturization. Advances in process technology demands on the electrical and thermal characteristics of the devices leading to complex structures. The entrance of SiC devices in the market has enormously improved energy efficiency in a wide range of industries, including lighting, electronics and telecommunications. It allows components to operate at substantially higher temperatures, voltages and power levels than silicon. This translates into smaller, lighter, simpler electrical systems. High avalanche breakdown field (1.0 – 3.0MV/cm), high thermal conductivity (5W/cm-oC) and high electric field strength for SiC makes it alternative material for high voltage, high power devices. For 3C-SiC Lateral Double Diffusion MOSFET, different parameters such as flat band voltage, bulk potential, mobility, body-effect term, transconductance etc. which depend on the doping concentration of the device are calculated and their variation with doping concentration is plotted. It was found that the electron mobility decreases with increase in doping concentration. However, it was noticed that the flat band voltage and bulk potential showed an increment with increase in the doping concentration. The I-V characteristics of LDMOS is obtained excluding the effect of fixed oxide charge in SiO2 layer. Furthermore, the effect of fixed oxide charge on flat band voltage is studied and a new approach to enhance the drain current is presented. The current in the device was found to increase due to reduction in flat band voltage, from 0.26A to 3A if fixed oxide charge is 6.76 × 10-8 Coulombs and doping concentration= 1015cm-3 and from 0.035A to 0.044A if fixed oxide charge is 6.76 × 10-8 Coulombs and doping concentration = 1017cm-3.
M. Tech. (VLSI Design and CAD)
Keywords: 3C-SiC; LDMOS